Strengthening Early Childhood Education and Care in Luxembourg. - OECD (Organization for Economic Cooperation & Development, 2022)
In supporting children's development, countries invest in the future successes of economies and societies. Awareness of the critical role early childhood education and care (ECEC) plays in setting a strong foundation for children's learning, development and well-being has grown among policy makers worldwide.